’Qiara’ of the Holy Quran and its impact upon Arabic literature - Safiuddin, M (IIUC Studies, 2009)
The full text of this article is in Arabic - see PDF below. doi: 10.3329/iiucs.v3i0.2674 IIUC STUDIES Vol. - 3, December 2006 (p 49-62)